Effectiveness of Disaster Management and Disaster Risk Reduction in Uganda. What are the challenges? - Budget Monitoring and Accountability Unit (Budget Monitoring and Accountability Unit, 2019)
The Government of Uganda (GoU) through the Second National Development Plan (NDP II) 2015/16 – 2019/20 prioritized reduction on the impact of natural disasters and emergencies though the following interventions:  Developing a disaster risk profile and vulnerability map of the country.  Coordinating the development and implementation of disaster mitigation and preparedness plans in all local governments (LGs).  Coordinating regular disaster vulnerability assessments at community level, hazard forecasting and dissemination of early warning messages.  Resettling landless communities and victims of disasters.  Coordinating timely responses to disasters and emergencies, and providing food and non-food relief to disaster victims.  Coordinating other state and non-state actors in fulfilling their mandates towards disaster issues. Disaster Management is defined as the organization and management of resources and responsibilities for dealing with all humanitarian aspects of emergencies, in particular preparedness, response and recovery in order to lessen the impact of disasters. Disaster risk reduction on the other hand is a systematic approach to identifying, assessing and reducing the risks of disaster. This policy brief examines the effectiveness of disaster management and disaster risk reduction, the challenges.